Is pulse modulation the future of laser technology in endourology: evidence from a literature review : section of EAU endourology : review - endo-urology - Corsini, Christian; Robesti, Daniele; Villa, Luca; Montorsi, Francesco; Pietropaolo, Amelia; Panthier, Frederic; Sierra, Alba; Juliebø-Jones, Patrick; Kwok, Jia-Lun; Tsaturyan, Arman; Contreras, Pablo; Fossati, Nicola; et al. (European urology focus, 2025)
Background and objective - The aim of our review was to comprehensively evaluate the impact of pulse modulation technology in the field of endourology, with a focus on laser lithotripsy and prostate enucleation. - Methods - A systematic search was conducted in the PubMed, MEDLINE, and Scopus databases for articles published during the past 20 yr (January 2004-July 2024). Article selection adhered to the Population, Intervention, Comparator, Outcome (PICO) framework and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. In vivo, ex vivo, in vitro, and clinical studies that reported on the impact of pulse modulation technologies in laser lithotripsy or prostate enucleation in comparison to a standard references or as a standalone report, with a focus on stone ablation efficiency, safety, tissue ablation, and hemostasis, were eligible. A total of 29 articles were included. - Key findings - Pulse modulation is a feature mostly implemented for Ho:YAG laser generators. Preclinical studies on pulse modulation have demonstrated promising results for both stone fragmentation and laser-tissue interaction. Clinical studies that investigated technologies such as the Vapor Tunnel, Virtual Basket, and Moses have revealed better efficiency in comparison to the short-pulse modality. While there have been modest improvements in hemostasis and operating time, there has been no obvious improvement in outcomes after prostate surgery. - Conclusions and clinical implications - While in vitro studies have shown that pulse modulation improves stone fragmentation, reduces retropulsion, and maintains thermal safety, clinical outcomes are more variable. For prostate enucleation, the benefits are less consistent. Pulse modulation may improve efficiency, primarily by reducing operating times, but key outcomes such as stone-free and complication rates remain comparable to those with standard modalities. - Patient summary - Our review shows that pulse modulation technology improves the effectiveness and safety of laser treatments for kidney stones. However, the benefits of this technology for prostate surgery are still uncertain, highlighting the need for more research.